Pengaruh Metode Ekstraksi Terhadap Kadar Flavonoid Total Daun Sukun (Artocarpus altilis (Park.) Fosberg) - Ulvia, Rengganis; Pratama, Nofran Putra; Nurjanah, Baiti (JOURNAL OF PHARMACEUTICAL (JOP), 2024)
Background: The breadfruit (Artocarpus altilis (Park) Fosberg.) is an Indonesian herbal plant that has long been used as a traditional medicine by the community, especially the leaves. Breadfruit leaves treat various diseases such as canker sores, hepatitis, inflammation, skin diseases, hypertension, asthma, fever, and aches and pains. Breadfruit leaves have various pharmacological properties, such as antiseptic, antibacterial, and antioxidant. This activity is related to the content of flavonoid compounds in breadfruit leaves. These flavonoid compounds can be obtained by extraction using conventional methods, namely maceration and non-conventional methods, namely Ultrasonic-Assisted Extraction (UAE). The choice of extraction method is an important factor in producing secondary metabolite compounds such as flavonoids. Objective: This study aims to determine the effect of extraction methods on total flavonoid levels in breadfruit leaves. Method: Breadfruit leaves were extracted using the maceration and UAE methods with 96% ethanol solvent at a ratio of 1:10 b/v. Qualitative tests were carried out using organoleptic tests and thin-layer chromatography (TLC) tests. Quantitative test by measuring the total flavonoid content of macerated and UAE breadfruit leaf extract using a UV-Vis spectrophotometer. The qualitative data obtained were then analyzed statistically using SPSS with Independent Samples T-Test with a confidence level of 95%. Results: The yield value of the maceration method was 11.8976% and the UAE method was 11.0854%. The results of the TLC test of breadfruit leaf extract produced an Rf value of 0.812 which was the same as the standard Rf value of quercetin, namely Rf 0.812 and the total flavonoid content produced by the UAE method was 44.689 ± 0.1764 mg QE / g extract, and the maceration method 42.3322 ± 0.3792 mg QE / g extract which was significantly different (p <0.05) Conclusion:  The extraction method influences the total flavonoid content in breadfruit leaves, whereas the UAE extraction method produces higher flavonoid levels than the maceration method.